Marginal adaptation of Class 2 adhesive restorations - Duarte Jr., Sillas; Saad, José Roberto Cury [UNESP] (My University, 2008)
Objective: Control of microleakage represents a challenge for posterior composite restorations. The technique for composite placement may reduce microleakage. The null hypothesis of this in vitro study was that centripetal incremental insertion of composite resin would result in less microleakage than that obtained with the oblique incremental technique or bulk technique. Method and Materials: Standardized Class 2 preparations were made in 60 caries-free extracted third molars and randomly assigned to 3 groups (n = 20): (1) oblique incremental insertion technique (control), (2) centripetal incremental insertion technique, and (3) bulk insertion. The teeth were restored with a total-etch adhesive and microhybrid composite resin. The specimens were isolated with nail varnish except for a 2-mmwide area around the restoration and then thermocycled (1,000 thermal cycles, 5°C/55°C; 30-second dwell time). The specimens were immersed in an aqueous solution of 50% silver nitrate for 24 hours, followed by 8 hours of immersion in a photo-developing solution and subsequently evaluated for leakage. The microleakage scores (0 to 4) obtained from the occlusal and cervical walls were analyzed with median nonparametric tests (P < .05). Results: The null hypothesis was rejected. All techniques attained statistically similar dentin microleakage scores (P = .15). The centripetal insertion technique displayed significantly less microleakage than the oblique technique at the enamel margins (P = .04). Conclusion: None of the techniques eliminated marginal microleakage in Class 2 preparations. However, in occlusal areas, the centripetal technique performed significantly better than the other techniques.
Keywords: Bulk; Centripetal placement; Class 2 composite resin; Dentin; Enamel; Marginal adaptation; Oblique placement